Integration of the socio-emotional learning model in engineering education - Franyelit Suárez-Carreño; Luis Rosales-Romero; Juan Carlos Hihuaña-Hallasi; Jean Carlo Díaz-Saravia; Miguel Pacheco-Quico; Iris Elena Aliaga-Villafuerte; Mario Otto Leonidas Paz-Zegarra; Armando Antonio Salinas Sanchez; Jose Calizaya-Lopez (Environment and Social Psychology, 2025)
This paper addresses novel perspectives on developing socio-emotional education across various educational levels, drawing on activities framed within Science, Technology, and Society (STS) and the computational thinking framework. Emotional integration as an educational innovation in curricula is a recent phenomenon responding to diverse societal needs and national developmental imperatives. This research aims to delve into the socioemotional aspects of the student, recognizing them as fundamental elements ensuring learning and competency development to achieve effective performance during and after the educational stage. The proposed criteria permit identifying contexts and learning environments conducive to students' social and emotional development. While also enhancing their achievement capacities. These capacities include motivation, self-regulation, self-efficacy, teamwork, social skills, cooperation, trust, empathy, and emotional management. Additionally, a survey was conducted to gain deeper insights into the factors influencing students' socioemotional states and how they affect their academic and professional performance. Finally, a model grounded in STS and computational thinking is presented, designed to contribute to students' socioemotional development across various educational levels, adaptable to science, engineering, and humanities disciplines.